The impact of change-, production-, employee-orientation leadership styles on employee engagement a study of Malaysia’s banking and financial institutions - Hew, Hui Ying (2025)
Employee engagement is widely recognized as a key driver of organizational efficiency and success. This is due to engaged employees who are committed to their roles and the organization, eventually foster higher morale, stronger unity, and greater workplace motivation. This study aimed to examine the relationship between change-orientation, production-orientation, and employee-orientation leadership styles and their impact on employee engagement among employees within an insurance institution in Kuala Lumpur, Malaysia. Using a quantitative approach, data was collected via a digital questionnaire from 248 employees, which represented a 95% response rate. Analysis using IBM SPSS Version 30.0 revealed that all three leadership styles had a positive and significant relationship with employee engagement. These findings suggest that organizations in dynamic sectors like insurance can enhance employee engagement by developing leaders with a balance of task focus, relational concern, and change agility. Future research is encouraged to explore broader internal and external factors influencing employee engagement, such as job resources, rewards, organizational support, career growth, interpersonal relationships, and work-life balance.